Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Dan Beban Kerja Terhadap Kinerja Karyawan Pada PT Indofood Kota Semarang - Salsa Naharani Nurjanah; Euis Soliha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research was designed to determine and analyse the influence of leadership style, work environment and workload on employee performance at PT Indofood Semarang City. This research uses leadership style, work environment, and workload as independent variables, employee performance as the dependent variable. This research uses primary data with a population of 834 employees of PT Indofood Semarang City. The sampling technique used in this research was purposive sampling technique. The data collection method in this research was using a questionnaire via Google Form. For the sample in this study 160 employees were taken by selecting employees on the morning shift. The analysis technique used in this research uses multiple linear analysis with the help of the SPSS version 25 test tool. The results of this research show that leadership style has a positive and significant effect on employee performance, the work environment has a positive and significant effect on employee performance, while workload has a no effect on employee performance. Keywords: Leadership Style, Work Environment, Workload, and Employee Performance